Optically anisotropic film, optical film, and display device

CN116964496BActive Publication Date: 2026-10-27FUJIFILM CORP
View PDF 91 Cites 0 Cited by

Patent Information

Application Number
CN202280015234.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-02-16
Filing Date
2022-02-14
Publication Date
2026-10-27
Estimated Expiration
2042-02-14

AI Technical Summary

Benefits of technology

[0024]根据本发明,能够提供一种对比度高且耐光性优异的光学各向异性膜、光学膜及显示装置。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116964496B_ABST
    Figure CN116964496B_ABST
Patent Text Reader

Abstract

An object of the present application is to provide an optically anisotropic film, an optical film, and a display device, which have high contrast and excellent light resistance. The optically anisotropic film of the present application contains a liquid crystalline compound and a dichroic substance, in which the liquid crystalline compound is vertically aligned and the dichroic substance forms an alignment structure, and in a cross section observed by a scanning transmission electron microscope, when the length of a long axis of the alignment structure is set as L and the length of a short axis is set as D, 16 or more of the alignment structures satisfying L ≥ 30 nm are observed per 40 μm 2 2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an optical anisotropic film, an optical film, and a display device. Background Technology

[0002] It is known that techniques are used in optical anisotropic films having an absorption axis in the thickness direction to prevent peeping into image display devices or to control viewing angles. For example, Patent Document 1 discloses a viewing angle control system that contains a dichroic material and has a polarizer (optical anisotropic film) with an angle of 0° to 45° between the absorption axis and the normal to the film surface.

[0003] Previous technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Application Publication No. 2009-145776 Summary of the Invention

[0006] The technical problem to be solved by the invention

[0007] The inventors studied the viewing angle control system described in Patent Document 1 and found that there is room for improvement in the difference between the transmittance from the front direction of the film and the transmittance from the tilt direction (hereinafter, "contrast"). Furthermore, the transmittance from the tilt direction, which has poor light resistance and is particularly helpful in preventing peeping, varies greatly.

[0008] Therefore, the objective of this invention is to provide an optical anisotropic film with high contrast and excellent lightfastness, an optical film, and a display device.

[0009] means for solving technical problems

[0010] As a result of in-depth research conducted by the inventors to achieve the above-mentioned problem, they discovered that by vertically aligning liquid crystal compounds and forming a specific number of dichroic materials with a predetermined size arrangement, the contrast of the optical anisotropic film is increased and the lightfastness is improved, thus completing the present invention.

[0011] That is, it was discovered that the above-mentioned task can be achieved through the following structure.

[0012] [1] An optically anisotropic film containing a liquid crystal compound and a dichroic substance, wherein the liquid crystal compound is vertically oriented and the dichroic substance forms an arrangement structure, and in a cross-section observed by a scanning transmission electron microscope, when the length of the major axis of the arrangement structure is set as L and the length of the minor axis is set as D, an arrangement structure satisfying L≥30nm is present in every 40μm. 2 More than 16 were observed in the study.

[0013] [2] According to the optical anisotropic film described in [1], wherein,

[0014] The proportion of arrangement structures in which the angle between the major axis of the arrangement structure and the normal direction of the optical anisotropic film is 20° or more is 28.0% or more.

[0015] [3] According to the optical anisotropic film described in [1], wherein,

[0016] An arrangement structure satisfying L≥240nm per 40μm 2 Less than 3 were observed.

[0017] [4] An optical film having:

[0018] Transparent film substrate; and

[0019] An optical anisotropic film as described in any one of [1] to [3] disposed on a transparent film substrate.

[0020] [5] The optical film according to [4] also has an orientation film between the transparent film substrate and the optical anisotropic film.

[0021] [6] The optical film according to [4] or [5] also has a polarizer having an absorption axis in the plane and is used to control the viewing angle.

[0022] [7] A display device having the optical film and display element described in [6].

[0023] Invention Effects

[0024] According to the present invention, an optical anisotropic film with high contrast and excellent lightfastness, an optical film, and a display device can be provided. Attached Figure Description

[0025] Figure 1 This is a conceptual diagram representing an example of a state in which the first dichroic substance and the second dichroic substance form an arranged structure.

[0026] Figure 2 This is a conceptual diagram representing an example of the arrangement of the first dichroic substance and the second dichroic substance.

[0027] Figure 3 This is a cross-sectional view conceptually representing an example of the optical anisotropic film of the present invention.

[0028] Figure 4 This is a scanning transmission electron microscope image of the cross-section of the optical anisotropic film produced in Example 1.

[0029] Figure 5 Is it using a specified threshold? Figure 4The image is generated by binarizing the brightness of a scanning transmission electron microscope image. Detailed Implementation

[0030] The present invention will now be described in detail.

[0031] The following description of the constituent elements is based on a representative embodiment of the present invention, but the present invention is not limited to this embodiment.

[0032] In addition, the numerical range indicated by “~” in this specification refers to the range including the lower and upper limits of the values ​​recorded before and after “~”.

[0033] Furthermore, in this specification, parallel, orthogonal, horizontal, and vertical refer to the ranges of parallel ±10°, orthogonal ±10°, horizontal ±10°, and vertical ±10°, respectively, rather than referring to parallel, orthogonal, horizontal, and vertical in a strict sense.

[0034] Furthermore, in this specification, each component may use a single substance corresponding to that component, or two or more substances may be used together. Where two or more substances are used together for each component, the content of that component, unless otherwise specified, refers to the total content of all substances used together.

[0035] Furthermore, in this specification, "(meth)acrylate" is the expression for "acrylate" or "methacrylate", "(meth)acrylate group" is the expression for "acrylate group" or "methacrylate group", and "(meth)acryloyl group" is the expression for "acryloyl group" or "methacryloyl group".

[0036] [Optical Anisotropic Films]

[0037] The optical anisotropic film of the present invention is an optical anisotropic film containing a liquid crystal compound and a dichroic substance, wherein the liquid crystal compound is vertically oriented and the dichroic substance is arranged in an array.

[0038] Furthermore, in the cross-section of the optical anisotropic film of the present invention observed by a scanning transmission electron microscope, when the length of the major axis of the above-mentioned arrangement structure is set as L and the length of the minor axis is set as D, the arrangement structure satisfying L≥30nm is present in every 40μm. 2 More than 16 were observed in the study.

[0039] In this invention, as described above, the liquid crystal compound is vertically oriented, and the dichroic material is at every 40 μm. 2 The film has more than 16 arrangement structures that satisfy L≥30nm, thereby increasing the contrast of the optical anisotropic film and improving its light resistance.

[0040] Although its details are not yet clear, the inventors speculate as follows.

[0041] First, it is believed that the contrast and lightfastness of optical anisotropic films are affected by the presence state of dichroic substances, which improve lightfastness by forming an arrangement structure.

[0042] Furthermore, it is believed that if the size of the arrangement structure of dichroic substances is too large (or the number is too many), light scattering will occur and the contrast will decrease. Conversely, if the size of the arrangement structure of dichroic substances is too small (or not formed or too few), the lightfastness will be low.

[0043] Therefore, the inventors can deduce that by arranging the structure within the above-mentioned range, an optical anisotropic film with high contrast and good light resistance can be obtained.

[0044] [Vertical orientation]

[0045] The optical anisotropic film of the present invention, as described above, has a liquid crystal compound vertically oriented.

[0046] Furthermore, the optical anisotropic film of the present invention preferably contains a dichroic material that is also oriented perpendicularly to the liquid crystal compound.

[0047] Here, vertical orientation means that the molecular axis of the liquid crystal compound (for example, the long axis in the case of rod-shaped liquid crystal compounds) is perpendicular to the main surface of the optically anisotropic film, but it is not required to be strictly perpendicular. It means that the angle between the average molecular axis of the liquid crystal compound in the optically anisotropic film and the main surface of the optically anisotropic film is less than 90 ± 10 degrees.

[0048] In addition, the above-mentioned tilt angle can be measured using AxoScan OPMF-1 (manufactured by Opto Science, Inc.).

[0049] Specifically, using an AxoScan OPMF-1 (manufactured by Opto Science, Inc.), the Mueller matrix of the optical anisotropic film was measured at wavelength λ at polar angles every 10 degrees between -50°C and 50°C. After removing the influence of surface reflection, the matrix was fitted with the following theoretical formula considering Snell and Fresnel forms to calculate the extinction coefficients ko[λ] (in-plane direction) and ke[λ] (thickness direction). Unless otherwise specified, the wavelength λ was set to 550 nm.

[0050] k = -log(T) × λ / (4πd)

[0051] Here, T represents transmittance, and d represents the thickness of the optical anisotropic film.

[0052] Based on the calculated ko[λ] and ke[λ], the absorbance and dichroism ratio in the in-plane and thickness directions can be calculated, thereby confirming whether the orientation is perpendicular.

[0053] [Arrangement Structure]

[0054] The optical anisotropic film of the present invention, as described above, has a dichroic material arranged in an array.

[0055] Here, arrangement structure refers to the state in which dichroic substances aggregate in an optically anisotropic film to form an aggregate, and the molecules of the dichroic substances are arranged periodically in the aggregate.

[0056] Furthermore, the arrangement structure can be formed solely by dichroic substances, or it can be formed by a liquid crystal compound and a dichroic substance.

[0057] Furthermore, the arrangement structure can be formed by one dichroic substance or by multiple dichroic substances.

[0058] Furthermore, the arrangement structure can be formed by a structure of one dichroic material and a structure of another dichroic material coexisting in an optically anisotropic film.

[0059] Furthermore, when the optical anisotropic film contains a variety of dichroic substances, the various dichroic substances contained in the optical anisotropic film can be arranged in an array, either all types of dichroic substances or only a portion of the dichroic substances.

[0060] Figure 1 This is a conceptual diagram illustrating an example of a state in which a first dichroic substance and a second dichroic substance form an arranged structure. The optically anisotropic film P contains molecules M of the first dichroic substance, molecules O of the second dichroic substance, and molecules L of a liquid crystal compound. For example... Figure 1 As shown, an aggregate G containing molecules M and O is formed. In aggregate G, the long axes of molecules M and O are arranged in the same direction, and molecules M and O are arranged in a periodically staggered manner with a width w.

[0061] The arrangement structure formed by the first dichroic substance and the second dichroic substance is not limited to Figure 1 The arrangement structure, for example, Figure 2 As shown, molecules M and O can be arranged in a periodically staggered manner at angle α.

[0062] Furthermore, in the optical anisotropic film of the present invention, as described above, when the length of the major axis of the arrangement structure is set as L and the length of the minor axis is set as D in the cross-section observed by scanning transmission electron microscopy, the arrangement structure satisfying L≥30nm per 40μm 2 More than 16 were observed in the study.

[0063] Figure 3 This is a cross-sectional view conceptually representing an example of the optical anisotropic film of the present invention.

[0064] exist Figure 3 In the diagram, the hollow parts represent the arrangement structure. Figure 3 In the example shown, the arrangement of the label N is an example that satisfies L≥30nm.

[0065] In this invention, the observation of cross-sections based on a scanning transmission electron microscope (hereinafter also referred to as "STEM") is specifically performed as follows.

[0066] First, using an ultrathin slicer, ultrathin slices with a thickness exceeding 100 nm are prepared along the thickness direction of the optical anisotropic film.

[0067] Next, the ultrathin slices were placed on a grid with a carbon support film for STEM observation.

[0068] Then, each grid was placed inside a scanning transmission electron microscope, and the cross-section was observed at an electron beam acceleration voltage of 30 kV.

[0069] Furthermore, the length L of the major axis and the length D of the minor axis of the arrangement structure are specifically measured as follows.

[0070] First, as described above, the cross-section of the optical anisotropic film is observed using STEM. The captured image is analyzed to create a frequency histogram, and the frequencies with the highest frequencies and the standard deviation of the frequency distribution are determined. Next, the frequency range from the highest frequency to 1.3 times the standard deviation on the darker side is set as a threshold. Then, using this threshold, a brightness-binarized image is created, and the portion of the dark region with a long axis greater than 30 nm is extracted as the arrangement structure.

[0071] Furthermore, each extracted arrangement structure is approximated by an ellipse. The length of the major axis of the approximate ellipse is set as the length L of the major axis of the arrangement structure, and the length of the minor axis of the approximate ellipse is set as the length D of the minor axis of the arrangement structure. Additionally, the angle between the axis perpendicular to the film surface (the normal direction of the optical anisotropic film) and the major axis of the approximate ellipse is set as the angle between the major axis of the arrangement structure and the normal direction of the optical anisotropic film.

[0072] The lengths L of the major axis and D of the minor axis of this arrangement can be determined using well-known image processing software. For example, the image processing software "ImageJ" can be cited as an example.

[0073] The optical anisotropic film of the present invention, as described above, when the length of the major axis of the arrangement structure is set as L and the length of the minor axis is set as D, provides an arrangement structure that satisfies L≥30nm per 40μm. 2 It has 16 or more, preferably 20 to 100, and more preferably 30 to 80.

[0074] Specifically, the image analysis described above is performed, within arbitrarily selected, non-repeating 13.58μm regions. 2 Area, 3 parts (total 40μm) 2 In the process, the arrangement structures that satisfy L≥30nm are extracted and counted.

[0075] In arbitrarily selected, non-repeating 40μm 2 (13.58μm 2 Count the arrangement structure in a region of 3 (×3) and 10 parts.

[0076] Then, the average number of arrangement structures in the 10 measured sites was calculated, and this average was set as the number of arrangement structures satisfying L≥30nm per 40μm. 2 The quantity in.

[0077] In addition, the actual measurement was 13.58 μm. 2 ×3=40.74μm 2 The region, but for convenience in this invention, the fraction is rounded and referred to as "every 40μm". 2 ".

[0078] In this invention, considering the need to further improve the contrast of optically anisotropic films, it is preferable to have an arrangement structure that satisfies L≥240nm per 40μm. 2 The observed number is less than 3, more preferably less than 1, and even more preferably no observation.

[0079] Furthermore, in this invention, considering the reasons for further improving the contrast and lightfastness of the optical anisotropic film, the proportion of the number of arrangement structures in which the angle between the long axis of the arrangement structure and the normal direction of the optical anisotropic film is 20° or more is preferably 28.0% or more, more preferably 50.0% or more, and even more preferably 70.0% or more.

[0080] <Associated Compounds>

[0081] In this invention, it is preferred that dichroic materials form an associative compound in the arrangement structure. By forming an associative compound, the contrast of the optically anisotropic film is further improved, and the lightfastness is further improved.

[0082] As a method for verifying the formation of associative compounds by dichroic substances, one could cite, for example, a method that compares the maximum absorption wavelength measured using the formed membrane with the maximum absorption wavelength of the solution.

[0083] As a method for determining the maximum absorption wavelength using the formed film, the following method can be specifically cited: a vertically oriented film of thickness (10 μm or more) is prepared, the film is cut, and the absorption spectrum of its cross section is measured using an instrument such as MSV-5200 (manufactured by JASCO Corporation).

[0084] Furthermore, as a method different from the method of determining the maximum absorption wavelength using the formed film, the following method can be cited: using the composition for forming the optical anisotropic film of the present invention, except that no orientation is performed, a film formed by the same method as the optical anisotropic film of the present invention is prepared, and the absorption spectrum of the film is measured. Additionally, as a method to prevent the composition for forming the optical anisotropic film from being oriented, methods for controlling orientation can be cited, such as adjusting the presence or amount of the orientation agent or surface modifier described later, or the presence or alteration of the orientation film described later.

[0085] Here, in the case of a sufficiently diluted solution, the maximum absorption wavelength of the solution is considered to be the maximum absorption wavelength of the dichroic substance alone (the dichroic substances do not interact with each other).

[0086] On the other hand, when the maximum absorption wavelength measured using a membrane differs from the maximum absorption wavelength of the solution, it is considered to be the interaction between dichroic substances and other substances (i.e., the formation of associated compounds).

[0087] Specifically, the maximum absorption wavelength λs in the absorption spectrum of the solution obtained by dissolving the dichroic substance is determined. In this case, the concentration of the diluted solution is preferably 3.0% or less, more preferably 2.0% or less.

[0088] Next, a liquid crystal composition containing at least a liquid crystal compound and a dichroic substance is cast onto a substrate (e.g., blue glass). The film F for measuring the maximum absorption wavelength is formed by heating and curing under ultraviolet light using the same method as the optical anisotropic film of the present invention. Furthermore, the absorption spectrum of film F is measured at a 0.5 nm pitch within a wavelength range of 380–800 nm to determine the maximum absorption wavelength λf.

[0089] Based on the above λs and λf satisfying the following equation (D), and considering the reasons shown below, it can be concluded that dichroic substances form associative compounds in their arrangement structure.

[0090] |λs-λf|≥2.0nm (D)

[0091] That is, the absorption spectrum of the solution formed by dissolving the dichroic substance is interpreted as the absorption spectrum of one molecule of the dichroic substance. Therefore, if the maximum absorption wavelength λs of the absorption spectrum and the maximum absorption wavelength λf of the absorption spectrum of the membrane F satisfy the above equation (D), it can be said that the maximum absorption wavelength shifts due to the association of the dichroic substance in the membrane F.

[0092] <Crystal Structure>

[0093] In this invention, it is preferable that the dichroic material forms a crystalline structure in its arrangement. By forming a crystalline structure, the contrast of the optically anisotropic film is further improved, and its lightfastness is further enhanced.

[0094] As a method for verifying that a dichroic material has a crystalline structure, one example is the method based on X-ray diffraction (XRD) spectra measured using optically anisotropic films.

[0095] In addition, in the following description, when manufacturing each film (optically anisotropic film) for comparison XRD spectra, the type of dichroic substance contained in each film is changed. In addition, care should be taken to ensure that the type of the substrate (e.g., the base material), the concentration of the composition and the coating conditions are consistent, and that the area and thickness of the film are the same.

[0096] Specifically, X-ray diffraction analysis of optically anisotropic films is performed using the in-plane method. Furthermore, the X-ray diffraction analysis performed using the in-plane method will be referred to as "in-plane XRD" below.

[0097] In-plane XRD is performed by irradiating the surface of the polarizer layer with X-rays using a thin-film X-ray diffraction device.

[0098] Using an appropriate in-plane orientation as a reference, in-plane XRD is performed in all directions at 15° scales. φ-scanning is performed on the observed peaks to determine the orientation in the substrate plane where the peak intensity is greatest. Using the in-plane spectra measured in the obtained orientation, the XRD spectra of a film laminated to the alignment film (described later) are compared with those of a film on which the optical anisotropic film of the present invention is laminated, or the XRD spectra of a film from which the dichroic material (described later) is removed from the optical anisotropic film of the present invention are compared with those of a film on which the optical anisotropic film of the present invention is laminated. This allows verification that the dichroic material forms a crystalline structure.

[0099] The transmittance of the front side of the optical anisotropic film of the present invention is preferably 65% ​​or more, more preferably 70% or more, and even more preferably 75% or more. This improves the illuminance of the image display device and enhances visibility.

[0100] Furthermore, in terms of enabling the hue in the front direction to be set to neutral, the orientation degree at 420 nm of the optical anisotropic film of the present invention preferably satisfies 0.93 or higher.

[0101] Tone control in optical films containing dichroic substances is typically achieved by adjusting the amount of dichroic substance added to the film. However, it is known that simply adjusting the amount of dichroic substance added cannot neutralize the tone in both the front and tilted directions. The reason for this inability to neutralize the tone in both directions is the low orientation at 420nm. By increasing the orientation at 420nm, it is possible to neutralize the tone in both directions.

[0102] [Liquid Crystal Composition]

[0103] The optical anisotropic film of the present invention can be formed using a liquid crystal composition containing a liquid crystal compound and a dichroic substance.

[0104] Furthermore, the liquid crystal composition may contain solvents, polymerization initiators, surface modifiers, alignment agents, and other components.

[0105] The following is a description of each component.

[0106] <Liquid Crystal Compounds>

[0107] The liquid crystal composition contains a liquid crystal compound. By containing the liquid crystal compound, the precipitation of dichroic substances can be suppressed, and the dichroic substances can be oriented with a high degree of orientation.

[0108] Liquid crystal compounds are liquid crystal compounds that do not exhibit dichroism.

[0109] As a liquid crystal compound, either a low-molecular-weight liquid crystal compound or a high-molecular-weight liquid crystal compound can be used, but a high-molecular-weight liquid crystal compound is more preferred for obtaining a high degree of orientation. Here, "low-molecular-weight liquid crystal compound" refers to a liquid crystal compound that does not have repeating units in its chemical structure. And "high-molecular-weight liquid crystal compound" refers to a liquid crystal compound that has repeating units in its chemical structure.

[0110] Examples of low-molecular-weight liquid crystal compounds include those described in Japanese Patent Application Publication No. 2013-228706.

[0111] Examples of polymeric liquid crystal compounds include the thermotropic liquid crystal polymer described in Japanese Patent Application Publication No. 2011-237513. Furthermore, the polymeric liquid crystal compound may have crosslinking groups (e.g., acryloyl and methacryloyl groups) at its ends.

[0112] Liquid crystal compounds can be used alone or in combination of two or more.

[0113] From the perspective of achieving better orientation of optically anisotropic films, liquid crystal compounds preferably include polymeric liquid crystal compounds.

[0114] Considering the superior orientation of dichroic materials, liquid crystal compounds are preferably polymeric liquid crystal compounds containing repeating units (hereinafter also referred to as "repeating units (3-1)") represented by the following formula (3-1).

[0115] [Chemical Formula 1]

[0116]

[0117] In the above formula (3-1), P1 represents the main chain of the repeating unit, L1 represents the single bond or divalent linker, SP1 represents the spacer group, M1 represents the mesocrystalline group, and T1 represents the terminal group.

[0118] In the repeating unit (3-1), the difference between the logP values ​​of P1, L1, and SP1 and the logP value of M1 is preferably 4 or more. More preferably, it is 4.5 or more. Since the logP values ​​of the main chain, L1, and spacer groups differ from the log value of the mesocrystalline group by a predetermined value or more, the structure from the main chain to the spacer groups is in a state of low compatibility with the mesocrystalline groups. Therefore, it can be inferred that the crystallinity of the polymeric liquid crystal compound is high, and the polymeric liquid crystal compound is in a state of high orientation. Thus, it can be inferred that if the orientation of the polymeric liquid crystal compound is high, the compatibility of the polymeric liquid crystal compound with dichroic substances decreases (i.e., the crystallinity of the dichroic substance increases) and the orientation of the dichroic substance increases. As a result, it is believed that the orientation of the obtained optical anisotropic film is high.

[0119] As the main chain of the repeating unit represented by P1, specifically, for example, groups represented by the following formulas (P1-A) to (P1-D) can be cited, wherein, from the viewpoint of the diversity of monomers that can be used as raw materials and ease of handling, the group represented by the following formula (P1-A) is preferred.

[0120] [Chemical Formula 2]

[0121]

[0122] In equations (P1-A) to (P1-D), "*" indicates the bonding position with L1 in equation (3-1).

[0123] In the above formulas (P1-A) to (P1-D), R 1 R 2 R 3 and R 4Each of the above-mentioned alkyl groups independently represents a hydrogen atom, a halogen atom, a cyano group, or an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms. The alkyl group can be a straight-chain or branched alkyl group, or an alkyl group having a cyclic structure (cycloalkyl). Furthermore, the alkyl group preferably has 1 to 5 carbon atoms.

[0124] The group represented by the above formula (P1-A) is preferably a unit of a partial structure of poly(meth)acrylate obtained by polymerization of (meth)acrylate.

[0125] The group represented by the above formula (P1-B) is preferably an ethylene glycol unit formed by ring-opening polymerization of the epoxy group of a compound having an epoxy group.

[0126] The group represented by the above formula (P1-C) is preferably a propylene glycol unit formed by ring-opening polymerization of an oxetane compound having an oxetane.

[0127] The group represented by the above formula (P1-D) is preferably a siloxane unit of a polysiloxane obtained by polycondensation of a compound having at least one of alkoxysilyl and silanol groups. Here, as a compound having at least one of alkoxysilyl and silanol groups, an example is a compound having the formula SiR 14 (OR 15 Compounds containing a group represented by )2-. In the formula, R 14 The meaning of R in (P1-D) 14 The meanings are the same, multiple R 15 Alkyl groups, which can be independently represented by 1 to 10 hydrogen or carbon atoms respectively.

[0128] L1 represents a single bond or a divalent linker.

[0129] Examples of divalent linker bases represented by L1 include -C(O)O-, -OC(O)-, -O-, -S-, and -C(O)NR. 3 -、-NR 3 C(O)-, -SO2- and -NR 3 R 4 - etc. In the formula, R 3 and R 4 Each of the following can be independently represented: a hydrogen atom and an alkyl group having 1 to 6 carbon atoms, which may have substituents (described later).

[0130] When P1 is a group represented by formula (P1-A), from the perspective of superior orientation of optical anisotropic films, L1 is preferably a group represented by -C(O)O-.

[0131] When P1 is a group represented by formulas (P1-B) to (P1-D), L1 is preferably a single bond, considering the superior orientation of the optically anisotropic film.

[0132] For reasons such as ease of liquid crystal properties or availability of raw materials, the spacer group represented by SP1 preferably includes at least one structure selected from the group consisting of ethylene oxide structure, propylene oxide structure, polysiloxane structure and fluorinated alkylene structure.

[0133] Here, the oxyethylene structure represented by SP1 is preferably composed of *-(CH2-CH2O). n1 -* indicates a group. In the formula, n1 represents an integer from 1 to 20, and * represents the bonding position with L1 or M1 in the above formula (3-1). Considering the superior orientation of the optical anisotropic film, n1 is preferably an integer from 2 to 10, more preferably an integer from 2 to 4, and most preferably 3.

[0134] Furthermore, considering the superior orientation of optically anisotropic films, the oxypropylene structure represented by SP1 is preferably composed of *-(CH(CH3)-CH2O). n2 -* indicates a group. In the formula, n2 represents an integer from 1 to 3, and * indicates the bonding position with L1 or M1.

[0135] Furthermore, considering the superior orientation of optically anisotropic films, the polysiloxane structure represented by SP1 is preferably composed of *-(Si(CH3)2-O). n3 -* indicates a group. In the formula, n3 represents an integer from 6 to 10, and * indicates the bonding position with L1 or M1.

[0136] Furthermore, considering the superior orientation of optically anisotropic films, the fluorinated alkylene structure represented by SP1 is preferably composed of *-(CF2-CF2). n4 -* indicates a group. In the formula, n4 represents an integer from 6 to 10, and * indicates the bonding position with L1 or M1.

[0137] The mesocrystalline group represented by M1 refers to the group that represents the main framework of liquid crystal molecules that contribute to the formation of liquid crystals. Liquid crystal molecules exhibit liquid crystal properties, exhibiting an intermediate state (intermediate phase) between the crystalline state and the isotropic liquid state. There are no particular limitations regarding the mesocrystalline group; for example, one can refer to "Flussige Kristalle in Tabellen II" (VEB Deutsche Verlagfur Grundstoff Industrie, Leipzig, 1984), especially pages 7-16, and the description in "Liquid Crystal Handbook Editorial Committee," "Liquid Crystal Handbook" (Maruzen, 2000), especially Chapter 3.

[0138] As a mesocrystalline group, it is preferred, for example, to have at least one cyclic structure selected from the group consisting of aromatic hydrocarbon groups, heterocyclic groups and alicyclic groups.

[0139] Considering the superior orientation of optically anisotropic films, the mesocrystalline group preferably has aromatic hydrocarbon groups, more preferably has 2 to 4 aromatic hydrocarbon groups, and even more preferably has 3 aromatic hydrocarbon groups.

[0140] From the perspectives of liquid crystal properties, liquid crystal phase transition temperature adjustment, raw material availability and synthetic applicability, as well as superior orientation of optical anisotropic films, groups represented by the following formula (M1-A) or the following formula (M1-B) are preferred as mesocrystalline groups, and groups represented by formula (M1-B) are more preferred.

[0141] [Chemical Formula 3]

[0142]

[0143] In formula (M1-A), A1 is a divalent group selected from the group consisting of aromatic hydrocarbon groups, heterocyclic groups, and alicyclic groups. These groups may be substituted with alkyl, fluorinated alkyl, alkoxy, or substituents.

[0144] The divalent group represented by A1 is preferably a 4- to 6-membered ring. Furthermore, the divalent group represented by A1 can be a monocyclic ring or a fused ring.

[0145] * indicates the bonding position with SP1 or T1.

[0146] Examples of divalent aromatic hydrocarbon groups represented by A1 include phenylene, naphthylene, fluorene-diyl, anthracene-diyl, and tetraphenyl-diyl. From the perspective of the diversity of mesocrystalline framework design or the availability of raw materials, phenylene or naphthylene is preferred, and phenylene is more preferred.

[0147] The divalent heterocyclic group represented by A1 can be either aromatic or non-aromatic, but from the viewpoint of further improving the degree of orientation, a divalent aromatic heterocyclic group is preferred.

[0148] Examples of atoms other than carbon that constitute a divalent aromatic heterocyclic group include nitrogen, sulfur, and oxygen atoms. In cases where an aromatic heterocyclic group has multiple atoms constituting the ring other than carbon, these atoms can be the same or different.

[0149] Specific examples of divalent aromatic heterocyclic groups include pyridinyl (pyridin-diyl), pyridazinyl (pyridinyl), imidazole-diyl, thiophenyl (thiophen-diyl), quinolineyl (quinoline-diyl), isoquinolineyl (isoquinoline-diyl), oxazole-diyl, thiazole-diyl, oxadiazole-diyl, benzothiazole-diyl, benzothiadiazole-diyl, phthalimide-diyl, thienothiazole-diyl, thiazonothiazole-diyl, thienothiophene-diyl, and thienooxazole-diyl.

[0150] Specific examples of the divalent alicyclic group represented by A1 include cyclopentylene and cyclohexylene.

[0151] In formula (M1-A), a1 represents an integer from 1 to 10. When a1 is 2 or higher, multiple A1 values ​​can be the same or different.

[0152] In formula (M1-B), A2 and A3 are each independently a divalent group selected from the group consisting of aromatic hydrocarbon groups, heterocyclic groups, and alicyclic groups. Specific examples and preferred embodiments of A2 and A3 are the same as A1 in formula (M1-A), therefore their description is omitted.

[0153] In formula (M1-B), a2 represents an integer from 1 to 10. When a2 is 2 or more, multiple A2s can be the same or different, multiple A3s can be the same or different, and multiple LA1s can be the same or different. Considering the superior orientation of optical anisotropic films, a2 is preferably an integer of 2 or more, and more preferably 2.

[0154] In formula (M1-B), when a2 is 1, LA1 is a divalent linker. When a2 is 2 or more, the plurality of LA1s are independently either single bonds or divalent linkers, and at least one of the plurality of LA1s is a divalent linker. When a2 is 2, considering the superior orientation of the optical anisotropic film, it is preferable that one of the two LA1s is a divalent linker and the other is a single bond.

[0155] In formula (M1-B), examples of divalent linkers represented by LA1 include -O- and -(CH2). g -、-(CF2) g -、-Si(CH3)2-、-(Si(CH3)2O) g -、-(OSi(CH3)2) g-(g represents an integer from 1 to 10.), -N(Z)-, -C(Z)=C(Z')-, -C(Z)=N-, -N=C(Z)-, -C(Z)2-C(Z')2-, -C(O)-, -OC(O)-, -C(O)O-, -OC(O) O-, -N(Z)C(O)-, -C(O)N(Z)-, -C(Z)=C(Z')-C(O)O-, -OC(O)-C(Z)=C(Z')-, -C(Z)=N-, -N=C(Z)-, -C(Z)=C(Z')-C(O)N (Z”)-, -N(Z”)-C(O)-C(Z)=C(Z')-, -C(Z)=C(Z')-C(O)-S-, -SC(O)-C(Z)=C(Z')-, -C(Z)=NN=C(Z')- (Z, Z', Z” independently represent hydrogen, C1-C4 alkyl, cycloalkyl, aryl, cyano or halogen atom.), -C≡C-, -N=N-, -S-, -S(O)-, -S(O)(O)-, -(O)S(O)O-, -O(O)S(O)O-, -SC(O)- and -C(O)S-, etc.

[0156] Among them, considering the superior orientation of optically anisotropic films, -C(O)O- is preferred.

[0157] LA1 can also be a group composed of two or more of these groups.

[0158] Specific examples of M1 include the following structures. Additionally, in the following specific examples, "Ac" represents an acetyl group.

[0159] [Chemical Formula 4]

[0160]

[0161] [Chemical Formula 5]

[0162]

[0163] [Chemical Formula 6]

[0164]

[0165] [Chemical Formula 7]

[0166]

[0167] [Chemical Formula 8]

[0168]

[0169] [Chemical Formula 9]

[0170]

[0171] [Chemical Formula 10]

[0172]

[0173] Examples of terminal groups represented by T1 include hydrogen atoms, halogen atoms, cyano groups, nitro groups, hydroxyl groups, alkyl groups with 1 to 10 carbon atoms, alkoxy groups with 1 to 10 carbon atoms, alkylthio groups with 1 to 10 carbon atoms, alkoxycarbonyl groups with 1 to 10 carbon atoms, alkoxycarbonyl groups with 1 to 10 carbon atoms (ROC(O)-: R is an alkyl group), acyloxy groups with 1 to 10 carbon atoms, acylamino groups with 1 to 10 carbon atoms, alkoxycarbonylamino groups with 1 to 10 carbon atoms, sulfonylamino groups with 1 to 10 carbon atoms, aminosulfonyl groups with 1 to 10 carbon atoms, carbamoyl groups with 1 to 10 carbon atoms, sulfinyl groups with 1 to 10 carbon atoms, urea groups with 1 to 10 carbon atoms, and groups containing (meth)acryloyloxy groups. Examples of groups containing (meth)acryloyloxy groups include those represented by -LA (L represents a single bond or a linker. Specific examples of linkers are the same as L1 and SP1 described above. A represents a group represented by (meth)acryloyloxy).

[0174] Considering the superior orientation of the optically anisotropic film, T1 is preferably an alkoxy group with 1 to 10 carbon atoms, more preferably an alkoxy group with 1 to 5 carbon atoms, and even more preferably a methoxy group. These terminal groups can be further replaced by these groups or polymerizable groups described in Japanese Patent Application Publication No. 2010-244038.

[0175] Considering the superior orientation of the optically anisotropic film, the number of atoms in the main chain of T1 is preferably 1 to 20, more preferably 1 to 15, even more preferably 1 to 10, and particularly preferably 1 to 7. By having the number of atoms in the main chain of T1 be 20 or less, the orientation of the optically anisotropic film is further improved. Here, "main chain" in T1 refers to the longest molecular chain bonded to M1, and hydrogen atoms are not included in the number of atoms in the main chain of T1. For example, when T1 is n-butyl, the number of atoms in the main chain is 4, and when T1 is sec-butyl, the number of atoms in the main chain is 3.

[0176] Considering the superior orientation of the optically anisotropic film, the content of repeating units (3-1) is preferably 20 to 100% by mass relative to 100% by mass of the total repeating units in the polymeric liquid crystal compound.

[0177] In this invention, the content of each repeating unit contained in the polymeric liquid crystal compound is calculated based on the loading amount (mass) of each monomer used to obtain each repeating unit.

[0178] The polymeric liquid crystal compound may contain a single repeating unit (3-1) or two or more repeating units. If the polymeric liquid crystal compound contains two or more repeating units (3-1), it has advantages such as improved solubility in solvents and easier adjustment of the liquid crystal phase transition temperature. When it contains two or more repeating units (3-1), it is preferable that their total amount is within the above-mentioned range.

[0179] In the case where the polymeric liquid crystal compound contains two repeating units (3-1), considering the superior orientation of the optical anisotropic film, it is preferable that the terminal group represented by T1 in one (repeating unit A) is alkoxy and the terminal group represented by T1 in the other (repeating unit B) is a group other than alkoxy.

[0180] Considering the superior orientation of optically anisotropic films, the terminal group represented by T1 in the repeating unit B is preferably an alkoxycarbonyl, a cyano, or a group containing (meth)acryloyloxy, more preferably an alkoxycarbonyl or a cyano.

[0181] Considering the superior orientation of the optically anisotropic film, the ratio (A / B) of the content of the repeating unit A in the polymeric liquid crystal compound to the content of the repeating unit B in the polymeric liquid crystal compound is preferably 50 / 50 to 95 / 5, more preferably 60 / 40 to 93 / 7, and even more preferably 70 / 30 to 90 / 10.

[0182] <Repeating Unit (3-2)>

[0183] The polymeric liquid crystal compound of the present invention may further comprise a repeating unit represented by the following formula (3-2) (also referred to as "repeating unit (3-2)" in this specification). This provides advantages such as improved solvent solubility and ease of adjustment of the liquid crystal phase transition temperature.

[0184] The repeating unit (3-2) differs from the repeating unit (3-1) mentioned above in that it at least does not have a mesocrystalline group.

[0185] When the polymeric liquid crystal compound contains repeating unit (3-2), the polymeric liquid crystal compound is a copolymer of repeating unit (3-1) and repeating unit (3-2) (or a copolymer that also contains repeating unit A and repeating unit B), and can be any kind of polymer such as block polymer, alternating polymer, random polymer and graft polymer.

[0186] [Chemical Formula 11]

[0187]

[0188] In equation (3-2), P3 represents the main chain of the repeating unit, L3 represents a single bond or a divalent linker, SP3 represents a spacer group, and T3 represents a terminal group.

[0189] The specific examples of P3, L3, SP3 and T3 in equation (3-2) are the same as those of P1, L1, SP1 and T1 in equation (3-1) above.

[0190] From the viewpoint of improving the strength of optical anisotropic films, T3 in formula (3-2) preferably has polymerizable groups.

[0191] The content of repeating units (3-2) is preferably 0.5 to 40% by mass relative to 100% by mass of the total repeating units in the polymeric liquid crystal compound, more preferably 1 to 30% by mass.

[0192] The polymeric liquid crystal compound may contain a single repeating unit (3-2) or two or more repeating units. When two or more repeating units (3-2) are contained, it is preferable that their total amount is within the above-mentioned range.

[0193] (weight-average molecular weight)

[0194] Considering the superior orientation of optically anisotropic films, the weight-average molecular weight (Mw) of the polymeric liquid crystal compound is preferably 1,000 to 500,000, more preferably 2,000 to 300,000. As long as the Mw of the polymeric liquid crystal compound is within the above range, the polymeric liquid crystal compound is easy to process.

[0195] In particular, from the viewpoint of suppressing cracking during coating, the weight-average molecular weight (Mw) of the polymeric liquid crystal compound is preferably 10,000 or more, and more preferably 10,000 to 300,000.

[0196] Furthermore, from the viewpoint of temperature tolerance of orientation, the weight-average molecular weight (Mw) of the polymeric liquid crystal compound is preferably less than 10,000, and more preferably 2,000 or more but less than 10,000.

[0197] In this invention, the weight-average molecular weight and number-average molecular weight are values ​​determined by gel permeation chromatography (GPC).

[0198] • Solvent (eluent): N-methylpyrrolidone

[0199] • Device Name: TOSOH HLC-8220GPC

[0200] • Column: Connect 3 TOSOH TSKgelSuperAWM-H (6mm×15cm) for use.

[0201] Column temperature: 25℃

[0202] • Sample concentration: 0.1% by mass

[0203] • Flow rate: 0.35 ml / min

[0204] • Calibration curve: The calibration curve was obtained using seven samples of TSK standard polystyrene prepared by TOSOH with Mw = 2,800,000 to 1,050 (Mw / Mn = 1.03 to 1.06).

[0205] (Content of liquid crystal compounds)

[0206] The content of the liquid crystal compound relative to the total solid content of the liquid crystal composition is preferably 30-99% by mass, more preferably 50-98% by mass, and particularly preferably 60-95% by mass. By keeping the content of the liquid crystal compound within the above range, the orientation degree of the optical anisotropic film is further improved.

[0207] The content of liquid crystal compound in the optically anisotropic film relative to the total mass of the optically anisotropic film is preferably the same as the content of liquid crystal compound relative to the total solid content of the liquid crystal composition described above.

[0208] <Dichromatic substances>

[0209] The liquid crystal composition also contains dichroic substances.

[0210] In this invention, dichroic substances refer to pigments whose absorbance varies with direction. Dichroic substances may or may not exhibit liquid crystal properties.

[0211] There are no particular limitations on dichroic substances. Examples include visible light absorbing substances (dichroic pigments), luminescent substances (fluorescent substances, phosphorescent substances), ultraviolet light absorbing substances, infrared light absorbing substances, nonlinear optical substances, carbon nanotubes, and inorganic substances (such as quantum rods). Previously known dichroic substances (dichroic pigments) can be used.

[0212] Specifically, examples include paragraphs

[0067] to

[0071] of Japanese Patent Application Publication No. 2013-228706, paragraphs

[0008] to

[0026] of Japanese Patent Application Publication No. 2013-227532, paragraphs

[0008] to

[0015] of Japanese Patent Application Publication No. 2013-209367, paragraphs

[0045] to

[0058] of Japanese Patent Application Publication No. 2013-14883, paragraphs

[0012] to

[0029] of Japanese Patent Application Publication No. 2013-101328, paragraphs

[0009] to

[0017] of Japanese Patent Application Publication No. 2013-37353, and paragraphs

[0051] to

[0065] of Japanese Patent Application Publication No. 2013-37353. Japanese Patent Application Publication No. 2012-63387, paragraphs

[0049] to

[0073] ; Japanese Patent Application Publication No. 2012-63387, paragraphs

[0016] to

[0018] ; Japanese Patent Application Publication No. 2001-133630, paragraphs

[0009] to

[0011] ; Japanese Patent Application Publication No. 2011-215337, paragraphs

[0030] to

[0169] ; Japanese Patent Application Publication No. 2010-106242, paragraphs

[0021] to

[0075] ; Japanese Patent Application Publication No. 2010-215846, paragraphs

[0011] to

[0025] ; Japanese Patent Application Publication No. 2011-048311, paragraphs

[0017] to

[0069] ; Japanese Patent Application Publication No. 2011-21361... Paragraphs

[0013] to

[0133] of Japanese Publication No. 0, paragraphs

[0074] to

[0246] of Japanese Publication No. 2011-237513, paragraphs

[0005] to

[0051] of Japanese Publication No. 2016-006502, paragraphs

[0014] to

[0032] of Japanese Publication No. 2018-053167, paragraphs

[0014] to

[0033] of Japanese Publication No. 2020-11716, paragraphs

[0005] to

[0041] of International Publication No. 2016 / 060173, paragraphs

[0008] to

[0062] of International Publication No. 2016 / 136561, and paragraph

[0014] of International Publication No. 2017 / 154835. The substances described in paragraphs

[0033] ,

[0014] to

[0033] of International Publication No. 2017 / 154695,

[0013] to

[0037] of International Publication No. 2017 / 195833,

[0014] to

[0034] of International Publication No. 2018 / 164252,

[0021] to

[0030] of International Publication No. 2018 / 186503,

[0043] to

[0063] of International Publication No. 2019 / 189345,

[0043] to

[0085] of International Publication No. 2019 / 225468, and

[0050] to

[0074] of International Publication No. 2020 / 004106.

[0213] Furthermore, the following specific examples can be cited as examples of dichroic substances.

[0214] [Chemical Formula 12]

[0215]

[0216] [Chemical Formula 13]

[0217]

[0218] [Chemical Formula 14]

[0219]

[0220] In this invention, two or more dichroic materials may be used together. For example, from the viewpoint of making the formed optical anisotropic film close to black, it is preferable to use at least one dichroic material having a maximum absorption wavelength in the wavelength range of 370 to 550 nm and at least one dichroic material having a maximum absorption wavelength in the wavelength range of 500 to 700 nm.

[0221] From the viewpoint of further enhancing the effects of the present invention, the content of the dichroic substance relative to the total solid content (100% by mass) of the liquid crystal composition is preferably 7 to 70% by mass, more preferably 10 to 60% by mass, and even more preferably 13 to 50% by mass. When multiple dichroic substances are used together, the total amount of the multiple dichroic substances is preferably within the above range.

[0222] <Solvent>

[0223] From the viewpoint of operability, liquid crystal compositions preferably contain a solvent.

[0224] Examples of solvents include ketones (e.g., acetone, 2-butanone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, acetylacetone, etc.), ethers (e.g., dioxane, tetrahydrofuran, tetrahydropyran, dioxolane, tetrahydrofuran alcohol, cyclopentylmethyl ether, dibutyl ether, etc.), aliphatic hydrocarbons (e.g., hexane, etc.), alicyclic hydrocarbons (e.g., cyclohexane, etc.), aromatic hydrocarbons (e.g., benzene, toluene, xylene, tetrahydronaphthalene, trimethylbenzene, etc.), carbon halogens (e.g., dichloromethane, chloroform, dichloroethane, dichlorobenzene, 1,1,2,2-tetrachloroethane, chlorotoluene, etc.), and esters (e.g., methyl acetate, ethyl acetate, butyl acetate, diethyl carbonate, ethyl acetoacetate, n-amyl acetate, ethyl benzoate, benzyl benzoate, butyl carbitol acetate). Organic solvents such as diethylene glycol monoethyl ether acetate, isoamyl acetate, etc., alcohols (e.g., ethanol, isopropanol, butanol, cyclohexanol, furfuryl alcohol, 2-ethylhexanol, octanol, benzyl alcohol, ethanolamine, ethylene glycol, propylene glycol, diethylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, etc.), phenols (e.g., phenol, cresol, etc.), cellosolves (e.g., methyl cellosolve, ethyl cellosolve and 1,2-dimethoxyethane, etc.), cellosolve acetates, sulfoxides (e.g., dimethyl sulfoxide, etc.), amides (e.g., dimethylformamide and dimethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone, 1,3-dimethyl-2-imidazolium ketone, etc.) and heterocyclic compounds (e.g., pyridine, 2,6-dimethylpyridine, etc.) as well as water.

[0225] These solvents can be used individually or in combination of two or more.

[0226] Furthermore, considering that dichroic substances can easily form an alignment structure, the contrast of the formed optical anisotropic film is further improved, and the lightfastness is further improved, the boiling point is preferably 70°C or higher, more preferably 125°C or higher, and even more preferably 180°C or higher.

[0227] Furthermore, when using two or more solvents, it is preferable to include a solvent with a boiling point of 70°C or higher, more preferably a solvent with a boiling point of 125°C or higher, and especially preferably a solvent with a boiling point of 180°C or higher.

[0228] Furthermore, when using two or more solvents, it is preferable to use solvents with a boiling point of less than 180°C and solvents with a boiling point of 180°C or higher. The mass ratio of the total amount of the solvent with a boiling point of less than 180°C to the solvent with a boiling point of 180°C or higher is preferably 1:1 to 30:1, more preferably 2:1 to 20:1, and even more preferably 3:1 to 15:1.

[0229] Furthermore, although the reason why dichroic substances can easily form an arrangement structure by using the above-mentioned boiling point is unclear, the inventors speculate as follows.

[0230] First, it is believed that the arrangement structure of dichroic substances is formed during the orientation process of the liquid crystal compound in the optical anisotropic film as it moves within the film. Therefore, it is inferred that if a solvent with a high boiling point, as described above, is present, the solvent is likely to remain, while the dichroic substances are likely to move within the film, resulting in the formation of an arrangement structure.

[0231] Among these solvents, organic solvents are preferred, considering the ease of adjusting the length L of the long axis of the arrangement structure, the further improvement of the contrast of the formed optical anisotropic film, and the further improvement of the lightfastness. More preferably, at least one organic solvent with a boiling point of 140°C or higher (high-boiling-point solvent) is used. There is no particular upper limit to the boiling point of the above-mentioned high-boiling-point solvent, but it is generally below 300°C, preferably below 250°C.

[0232] As high-boiling-point solvents, the ketones, aromatic hydrocarbons, carbon halides, esters, alcohols, cellosols, sulfoxides, heterocyclic compounds, and amides mentioned above are preferred. Xylene, tetrahydronaphthalene, 1,1,2,2-tetrachloroethane, ethyl acetoacetate, n-amyl acetate, isoamyl acetate, benzyl alcohol, acetylacetone, hexanol, octanol, furfuryl alcohol, 2-ethylhexanol, ethanolamine, ethylene glycol, propylene glycol, butyl carbitol acetate, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether acetate, cyclohexanol, diethylene glycol, diethylene glycol monobutyl ether, ethyl benzoate, benzyl benzoate, dibutyl ether, phenol, cresol, dimethylacetamide, dimethylformamide, N-ethylpyrrolidone, dimethyl sulfoxide, pyridine, and 2,6-dimethylpyridine are more preferred.

[0233] When the liquid crystal composition contains a solvent, considering that the orientation degree of the formed optical anisotropic film becomes higher and the heat resistance is further improved, the solvent content relative to the total mass (100% by mass) of the liquid crystal composition is preferably 60 to 99.5% by mass, more preferably 70 to 99% by mass, and especially preferably 75 to 98% by mass.

[0234] <Polymerization Initiator>

[0235] Liquid crystal compositions may contain polymerization initiators.

[0236] There are no particular limitations on the polymerization initiator, but photosensitive compounds, i.e., photopolymerization initiators, are preferred.

[0237] As photopolymerization initiators, a wide variety of compounds can be used without particular limitation. Examples of photopolymerization initiators include α-carbonyl compounds (as described in U.S. Patent Nos. 2,367,661 and 2,367,670), azobin ethers (as described in U.S. Patent No. 2,448,828), α-hydrocarbon-substituted aromatic azobin compounds (as described in U.S. Patent No. 2,722,512), polynuclear quinone compounds (as described in U.S. Patent Nos. 3,046,127 and 2,951,758), and combinations of triarylimidazolium dimers and p-aminophenyl ketones (as described in U.S. Patent No. 3,549,367). (e.g., acridine and phenazine compounds (Japanese Patent Application Publication No. 60-105667, US Patent No. 4239850), oxadiazole compounds (US Patent No. 4212970), o-acyl oxime compounds (Japanese Patent Application Publication No. 2016-27384

[0065] ), and acylphosphine oxide compounds (Japanese Patent Application Publication No. 63-40799, Japanese Patent Application Publication No. 5-29234, Japanese Patent Application Publication No. 10-95788, and Japanese Patent Application Publication No. 10-29997), etc.

[0238] Commercially available products can also be used as photopolymerization initiators, such as IRGACURE-184, IRGACURE-907, IRGACURE-369, IRGACURE-651, IRGACURE-819, IRGACURE-OXE-01, and IRGACURE-OXE-02 manufactured by BASF.

[0239] When the liquid crystal composition contains a polymerization initiator, considering that the orientation degree of the formed optical anisotropic film becomes higher and the heat resistance is further improved, the content of the polymerization initiator relative to the total solid content (100% by mass) of the liquid crystal composition is preferably 0.01 to 30% by mass, more preferably 0.1 to 15% by mass.

[0240] <Polymerizing compounds>

[0241] Liquid crystal compositions may contain polymeric compounds.

[0242] Examples of polymerizable compounds include compounds containing acrylates (e.g., (meth)acrylate monomers).

[0243] In cases where the liquid crystal composition contains a polymerizable compound, from the viewpoint of further enhancing the effects of the present invention, the content of the polymerizable compound relative to the total solid content (100% by mass) of the liquid crystal composition is preferably 0.5 to 50% by mass, more preferably 1.0 to 40% by mass.

[0244] <Surface Modifier>

[0245] The liquid crystal composition preferably contains a surface modifier.

[0246] By incorporating surface modifiers, the smoothness of the coated surface can be improved, the orientation degree can be enhanced, or depressions and unevenness can be suppressed, and the in-plane uniformity can be improved.

[0247] Fluoro(meth)acrylate polymers described in Japanese Patent Application Publication No. 2007-272185,

[0018] to

[0043] , etc., can be used as surface modifiers. Other compounds besides these can also be used as surface modifiers. A single surface modifier can be used, or two or more can be used in combination.

[0248] When the liquid crystal composition contains a surface modifier, the content of the surface modifier in the liquid crystal composition is preferably 0.1 to 2.0% by mass relative to the total solid content of the liquid crystal composition, more preferably 0.1 to 1.0% by mass.

[0249] When the optical anisotropic film contains a surface modifier, the content of the surface modifier relative to the total mass of the optical anisotropic film is preferably the same as the content of the surface modifier relative to the total solid content of the liquid crystal composition.

[0250] <Orientation Agent>

[0251] Liquid crystal compositions may contain alignment agents.

[0252] Specifically, examples of orientation agents include boron oxides and onium salts, which are vertical orientation agents.

[0253] As a boric acid compound, the compound represented by formula (30) is preferred.

[0254] Equation (30)

[0255] [Chemical Formula 15]

[0256]

[0257] In equation (30), R 1 and R 2 Each of the following can be independently represented: a hydrogen atom, a substituted or unsubstituted aliphatic hydrocarbon group, a substituted or unsubstituted aryl group, or a substituted or unsubstituted heterocyclic group.

[0258] R 3 This indicates a substituent containing a (meth)acryloyl group.

[0259] As a specific example of boric acid compounds, one can cite the boric acid compounds represented by general formula (I) described in paragraphs 0023 to 0032 of Japanese Patent Application Publication No. 2008-225281.

[0260] The following compounds are also preferred as boric acid compounds.

[0261] [Chemical Formula 16]

[0262]

[0263] As a ium salt, the compound represented by formula (31) is preferred.

[0264] Equation (31)

[0265] [Chemical Formula 17]

[0266]

[0267] In formula (31), ring A represents a quaternary ammonium ion composed of a nitrogen-containing heterocycle. X represents an anion. L 1 This represents a binary linker. L 2 Represents a single bond or a divalent linker. Y 1 The symbol "Z" indicates a divalent linker with a 5- or 6-membered ring as part of the structure. The symbol "P" indicates a divalent linker with a 2- to 20-membered alkylene group as part of the structure. 1 and P 2 Each of these represents a monovalent substituent that has a polymerizable alkene unsaturated bond.

[0268] Specific examples of onium salts include those described in paragraphs 0052 to 0058 of Japanese Patent Application Publication No. 2012-208397, those described in paragraphs 0024 to 0055 of Japanese Patent Application Publication No. 2008-026730, and those described in Japanese Patent Application Publication No. 2002-37777.

[0269] When the liquid crystal composition contains an alignment agent, the content of the alignment agent in the liquid crystal composition is preferably 0.1 to 40% by mass, more preferably 0.3 to 20% by mass, relative to the total solid content (100% by mass) of the liquid crystal composition.

[0270] Furthermore, the orientation agent can be used alone or in combination of two or more. When using two or more orientation agents, it is preferable that their combined dosage is within the range described above.

[0271] [Manufacturing method of optical anisotropic films]

[0272] The method for manufacturing the optical anisotropic film of the present invention is not particularly limited, but considering that the degree of orientation of the obtained optical anisotropic film is higher, it is preferable to include the following steps in sequence (hereinafter also referred to as "the manufacturing method of the present invention"): a step of coating the above-mentioned liquid crystal composition onto an alignment film to form a coating film (hereinafter also referred to as "coating film forming step"); and a step of aligning the liquid crystal components contained in the above-mentioned coating film (hereinafter also referred to as "alignment step").

[0273] In addition, liquid crystal components refer to components that not only contain the aforementioned liquid crystal compounds but also contain dichroic substances with liquid crystal properties.

[0274] The following is a description of each process.

[0275] <Coating film formation process>

[0276] The coating film formation process involves coating the aforementioned liquid crystal composition onto an alignment film to form a coating film. The liquid crystal compound in the coating film is vertically aligned through the interaction between the alignment film and (in the case where the liquid crystal composition contains a vertical alignment agent) a vertical alignment agent.

[0277] By using a liquid crystal composition containing the aforementioned solvent or by using a substance that forms a liquid liquid such as a melt by heating, the liquid crystal composition can be easily coated onto an alignment film.

[0278] Commonly known methods for coating liquid crystal compositions include roller coating, gravure printing, spin coating, wire-wound coating, extrusion coating, direct gravure coating, reverse gravure coating, die coating, spray coating, and inkjet coating.

[0279] (Orientation film)

[0280] The alignment film can be any film as long as it is a film that vertically aligns the liquid crystal compounds contained in the liquid crystal composition.

[0281] Alignment films can be formed by methods such as friction treatment of the film surface of organic compounds (preferably polymers), tilted evaporation of inorganic compounds, formation of layers with microgrooves, or accumulation of organic compounds (e.g., ω-trisanoic acid, dioctadecylmethylammonium chloride, methyl stearate, etc.) based on the Langmuir-Blodgett process (LB film). Alignment films that generate alignment functions by applying an electric field, a magnetic field, or light irradiation are also known. In this invention, from the perspective of easily controlling the pretilt angle of the alignment film, an alignment film formed by friction treatment is preferred; from the perspective of alignment uniformity, a photo-alignment film formed by light irradiation is also preferred.

[0282] (1) Friction-treated orientation film

[0283] Polymer materials used in alignment films formed by friction processing have been described in numerous documents, and many commercially available products are readily available. In this invention, polyvinyl alcohol or polyimide and its derivatives are preferably used. Regarding the alignment film, reference can be made to the description on page 43, line 24 to page 49, line 8 of International Publication No. 2001 / 88574A1. The thickness of the alignment film is preferably 0.01 to 10 μm, more preferably 0.01 to 1 μm.

[0284] (2) Photoalignment film

[0285] Photoalignment materials for alignment films formed by light irradiation have been described in numerous documents. In this invention, preferred examples include, for instance, the azo dyes described in Japanese Patent Application Publication Nos. 2006-285197, 2007-76839, 2007-138138, 2007-94071, 2007-121721, 2007-140465, 2007-156439, 2007-133184, 2009-109831, Japanese Patent Nos. 3883848, and 4151746. Compounds, aromatic ester compounds described in Japanese Patent Application Publication No. 2002-229039, maleimides having photo-orientation units and / or alkenyl-substituted nadicimide compounds described in Japanese Patent Application Publication No. 2002-265541 and No. 2002-317013, photocrosslinkable silane derivatives described in Japanese Patent Nos. 4205195 and 4205198, photocrosslinkable polyimides, polyamides, or esters described in Japanese Patent Application Publication Nos. 2003-520878, 2004-529220, or 4162850. More preferably, azo compounds, photocrosslinkable polyimides, polyamides, or esters.

[0286] The photo-alignment film is manufactured by irradiating the photo-alignment film formed from the above materials with linearly polarized light or unpolarized light.

[0287] In this specification, "linearly polarized light irradiation" and "unpolarized light irradiation" refer to operations used to induce a photoreaction in a photo-alignment material. The wavelength of the light used varies depending on the photo-alignment material used, and is not particularly limited as long as it is the wavelength required for the photoreaction. The peak wavelength of the light used in the irradiation is preferably 200 nm to 700 nm, and more preferably ultraviolet light with a peak wavelength of 400 nm or less.

[0288] Light sources used in illumination can include commonly used light sources such as tungsten lamps, halogen lamps, xenon lamps, xenon flash lamps, mercury lamps, mercury-xenon lamps, and carbon arc lamps, as well as various lasers [e.g., semiconductor lasers, helium-neon lasers, argon-ion lasers, helium-cadmium lasers, and YAG (yttrium aluminum garnet) lasers], light-emitting diodes, and cathode ray tubes.

[0289] Methods for obtaining linearly polarized light include using polarizers (e.g., iodine polarizers, dichroic material polarizers, and wire-grid polarizers), using prism-like elements (e.g., Glan-Thomson prisms), using reflective polarizers with Brewster angles, or using light emitted from a laser source with polarized light. Furthermore, filters or wavelength conversion elements can be used to selectively illuminate only the desired wavelength of light.

[0290] When the irradiated light is linearly polarized, a method is used to irradiate the alignment film from the top surface or from the back surface, either perpendicularly or obliquely. The incident angle of the light varies depending on the photoalignment material, preferably 0–90° (perpendicular), and more preferably 40–90°.

[0291] In the case of unpolarized light, unpolarized light is irradiated at an angle towards the alignment film. The incident angle is preferably 10 to 80°, more preferably 20 to 60°, and particularly preferably 30 to 50°.

[0292] The irradiation time is preferably 1 minute to 60 minutes, more preferably 1 minute to 10 minutes.

[0293] When patterning is required, the method of applying light through a photomask to create the pattern the required number of times can be used, or the pattern can be written by laser scanning.

[0294] <Orientation Process>

[0295] The alignment process is a process of orienting the dichroic material contained in the coated film. This allows the optical anisotropic film of the present invention to be obtained. It is understood that in the alignment process, the dichroic material is aligned along the liquid crystal compound oriented through the alignment film.

[0296] The orientation process may include a drying process. This drying process removes components such as solvents from the coated film. The drying process can be performed by placing the coated film at room temperature for a specified time (e.g., natural drying), or by heating and / or air supply.

[0297] Here, the dichroic substances contained in the liquid crystal composition are sometimes oriented through the above-described coating film formation process or drying treatment. For example, sometimes in the process of preparing the liquid crystal composition into a coating liquid containing a solvent, the solvent is removed from the coating film by drying the coating film, thereby orienting the dichroic substances contained in the coating film and obtaining the optical anisotropy film of the present invention.

[0298] The orientation process preferably includes heat treatment. As a result, the dichroic substances contained in the coated film are further oriented, and the degree of orientation of the obtained optically anisotropic film becomes higher.

[0299] From the perspective of manufacturing applicability, the heat treatment is preferably 10–250°C, more preferably 25–190°C. Furthermore, the heating time is preferably 1–300 seconds, more preferably 1–60 seconds.

[0300] The alignment process can include a cooling process performed after the heat treatment. The cooling process involves cooling the heated coating film to approximately room temperature (20–25°C). This further fixes the orientation of the dichroic material contained in the coating film, and the resulting optically anisotropic film exhibits a higher degree of orientation. There are no particular limitations on the cooling method; it can be implemented using known methods.

[0301] Through the above processes, the optical anisotropic film of the present invention can be obtained.

[0302] In this invention, the technique for orienting dichroic materials in a desired direction can be referenced from the fabrication techniques of polarizers using dichroic materials or the fabrication techniques of host-guest liquid crystal cells. For example, the techniques used in the fabrication methods of dichroic polarizing elements described in Japanese Patent Application Publication Nos. 11-305036 and 2002-90526, and the fabrication methods of host-guest type liquid crystal display devices described in Japanese Patent Application Publication Nos. 2002-99388 and 2016-27387, can also be used in the fabrication of the optical anisotropic film of this invention.

[0303] For example, using the technique of guest-host type liquid crystal cells, the dichroic material can be oriented as desired as described above, depending on the orientation of the host liquid crystal. Specifically, by mixing the dichroic material as the guest and the rod-shaped liquid crystal compound as the host liquid crystal, the host liquid crystal is oriented, and the molecular orientation of the dichroic material is fixed along with the orientation of its liquid crystal molecules, thereby fixing its orientation state, and thus the optical anisotropic film of the present invention can be produced.

[0304] In this invention, to prevent changes in the light absorption characteristics of the optically anisotropic film due to the operating environment, it is preferable to fix the orientation of the dichroic material by forming a chemical bond. For example, the orientation can be fixed by polymerizing the main liquid crystal, the dichroic material, or a polymerizable component to be added as desired.

[0305] Furthermore, by permeating the dichroic substance into the polymer film and aligning it along the orientation of the polymer molecules in the polymer film, a polymer film capable of meeting the light absorption characteristics required for the optically anisotropic film used in this invention can be fabricated. Specifically, a solution of the dichroic substance can be coated onto the surface of the polymer film and permeated into the film. The orientation of the dichroic substance can be adjusted according to the orientation of the polymer chains in the polymer film, its properties (chemical and physical properties of the polymer chains or their functional groups), coating method, etc. Detailed information about this method is described in Japanese Patent Application Publication No. 2002-90526.

[0306] <Other Processes>

[0307] This manufacturing method may include a step (hereinafter also referred to as the "curing step") after the above-mentioned alignment step to cure the optically anisotropic film.

[0308] The curing process is carried out, for example, by heating and / or light irradiation (exposure). Preferably, the curing process is carried out by light irradiation.

[0309] The light source used for curing can be various types of light sources such as infrared, visible light, or ultraviolet light, but ultraviolet light is preferred. Furthermore, ultraviolet light can be irradiated while heating is being performed during curing, or ultraviolet light can be irradiated through a filter that allows only specific wavelengths to be transmitted.

[0310] Furthermore, exposure can be performed under a nitrogen atmosphere. In the case of curing optically anisotropic films via free radical polymerization, the polymerization hindrance caused by oxygen can be reduced, therefore exposure under a nitrogen atmosphere is preferred.

[0311] [Optical film]

[0312] The optical film of the present invention has a transparent film substrate and the aforementioned optical anisotropic film disposed on the transparent film substrate.

[0313] Furthermore, the optical film of the present invention may have an orientation film between the transparent film substrate and the optical anisotropic film.

[0314] Furthermore, the optical film of the present invention may also have a polarizer having an in-plane absorption axis. The polarizer is preferably disposed on the side of the optical anisotropic film opposite to the transparent substrate film. The polarizer may be configured to contact the surface of the optical anisotropic film, or it may be disposed on the surface of the optical anisotropic film via other layers (e.g., known adhesive layers or bonding layers). When the optical film of the present invention has the aforementioned polarizer, the optical film of the present invention is preferably a viewing angle control film for controlling the viewing angle.

[0315] The components constituting the optical film of the present invention will be described below.

[0316] [Transparent film substrate]

[0317] As a transparent film substrate, known transparent resin films, transparent resin sheets, transparent resin plates, etc., can be used, without particular limitation. As a transparent resin film, cellulose acylate films (e.g., cellulose triacetate films (refractive index 1.48), cellulose diacetate films, cellulose acetate butyrate films, cellulose acetate propionate films), polyethylene terephthalate films, polyethersulfone films, polyacrylic acid resin films, polyurethane resin films, polyester films, polycarbonate films, polysulfone films, polyether films, polymethylpentene films, polyetherketone films, (meth)acrylonitrile films, etc., can be used.

[0318] Among them, cellulose acylate films, which are commonly used as protective films for polarizers, are preferred due to their high transparency, low optical birefringence, and ease of manufacture. Cellulose triacetate films are particularly preferred.

[0319] The thickness of the transparent film substrate is typically 20μm to 100μm.

[0320] In this invention, it is particularly preferred that the transparent film substrate is a cellulose ester film with a film thickness of 20 to 70 μm.

[0321] [Optical anisotropic films]

[0322] Regarding the optical anisotropic film of the present invention, as described above, its description is therefore omitted.

[0323] [Orientation film]

[0324] Regarding the alignment film (alignment layer), as described above, its description is omitted.

[0325] [Blocking layer]

[0326] The optical film of the present invention preferably has a blocking layer together with the transparent film substrate and the light absorption anisotropic layer.

[0327] Here, the barrier layer is also called the gas barrier layer (oxygen barrier layer), which has the function of protecting the polarization element of the present invention from gases such as oxygen in the atmosphere, moisture or compounds contained in adjacent layers.

[0328] Regarding the barrier layer, for example, reference can be made to paragraphs

[0014] to

[0054] of Japanese Patent Application Publication No. 2014-159124, paragraphs

[0042] to

[0075] of Japanese Patent Application Publication No. 2017-121721, paragraphs

[0045] to

[0054] of Japanese Patent Application Publication No. 2017-115076, paragraphs

[0010] to

[0061] of Japanese Patent Application Publication No. 2012-213938, and paragraphs

[0021] to

[0031] of Japanese Patent Application Publication No. 2005-169994.

[0329] [Color Adjustment Layer]

[0330] The optical film of the present invention preferably comprises a tone adjustment layer having at least one pigment compound. The pigment compound contained in the tone adjustment layer is preferably in a non-oriented state.

[0331] When adjusting the amount of pigment in the light absorption anisotropic layer, the hue change observed from the tilt direction relative to the transmittance central axis becomes larger. However, by adjusting the hue using a hue adjustment layer, the hue change in the tilt direction relative to the transmittance central axis can be suppressed.

[0332] This tone adjustment layer can have only the function of a tone adjustment layer, or it can have the function of being integrated with other layers.

[0333] The absorption peak wavelength of the pigment compound contained in the hue adjustment layer used in this invention is preferably 500 nm or more and 650 nm or less, more preferably 550 nm or more and 600 nm or less. By setting the absorption of the pigment compound within this range, the hue of the optical film in this invention can be adjusted to be more neutral.

[0334] Examples of pigment compounds contained in the hue adjustment layer include azo, methine, anthraquinone, triarylmethane, oxazine, methylimine, phthalocyanine, porphyrin, perylene, pyrrolopyrrole, and squaric acid cyanine. From the viewpoint of excellent absorption waveform, heat resistance, and lightfastness, azo, phthalocyanine, and anthraquinone are preferred, with anthraquinone being particularly preferred. Examples of pigment compounds described in the book "Functional Pigments" co-authored by Nobuoshi Okawahara, Ken Matsuoka, Tsuneaki Hirashima, and Teijiro Kitao, published in 1992 by Kodansha Ltd., and "Electronic Related Materials" edited by Sumio Tokita, published in 1998 by CMC Publishing Co., Ltd., published in 1998 by Sumio Tokita, are also mentioned.

[0335] The following are specific examples of pigment compounds used in this invention, but the invention is not limited to these.

[0336] Anthraquinone

[0337] [Chemical Formula 18]

[0338]

[0339] azo

[0340] [Chemical Formula 19]

[0341]

[0342] Triarylmethane

[0343] [Chemical Formula 20]

[0344]

[0345] Oxazine

[0346] [Chemical Formula 21]

[0347]

[0348] Phthalocyanine

[0349] [Chemical Formula 22]

[0350]

[0351] [Polarizer]

[0352] The polarizer used in this invention is not particularly limited as long as it is a component that has an absorption axis in the plane and has the function of converting light into linearly polarized light in a specific way; conventionally known polarizers can be used. Iodine-based polarizers, dye-based polarizers utilizing dichroic dyes, and polyene-based polarizers can be used as polarizers. Iodine-based polarizers and dye-based polarizers include both coated polarizers and stretched polarizers, all of which are applicable.

[0353] As a polarizer, a polarizer that orients dichroic organic pigments by utilizing the orientation of liquid crystal compounds is preferred. As a stretching polarizer, a polarizer made by adsorbing iodine or dichroic dyes onto polyvinyl alcohol and stretching it is preferred.

[0354] For example, the light-absorbing anisotropic layer containing a two-color pigment compound with horizontal orientation (the direction intersecting with the thickness direction of the optical anisotropic film) but without liquid crystal compound, as described in Japanese Patent Application Publication No. 2010-152351, and the light-absorbing anisotropic layer containing a liquid crystal compound and a two-color pigment compound with horizontal orientation, as described in International Patent Application Publication No. 2017 / 154907, are examples.

[0355] Furthermore, as a method for obtaining a polarizer by stretching and dyeing a laminated film in which a polyvinyl alcohol layer is formed on a substrate, examples include Japanese Patent No. 5048120, Japanese Patent No. 5143918, Japanese Patent No. 5048120, Japanese Patent No. 4691205, Japanese Patent No. 4751481, and Japanese Patent No. 4751486, and known technologies related to these polarizers can be preferred.

[0356] Here, horizontal orientation means that the molecular axis of the liquid crystal compound or dichroic pigment compound (e.g., the long axis in the case of rod-shaped liquid crystal compounds) is parallel to the main surface of the polarizer, but strict parallelism is not required. It means that the tilt angle between the average molecular axis of the liquid crystal compound or dichroic pigment compound in the polarizer and the main surface of the polarizer is less than ±10 degrees. Furthermore, the above tilt angle can be measured using an AxoScan OPMF-1 (manufactured by Opto Science, Inc.).

[0357] Specifically, using an AxoScan OPMF-1 (manufactured by Opto Science, Inc.), the Mueller matrix of the polarizer at wavelength λ was measured every 10 degrees at the polar angle between -50°C and 50°C. After removing the influence of surface reflection, the matrix was fitted with the following theoretical formula considering Snell and Fresnel modes to calculate the extinction coefficients ko[λ] (in-plane direction) and ke[λ] (thickness direction). Unless otherwise specified, the wavelength λ was set to 550 nm.

[0358] k = -log(T) × λ / (4πd)

[0359] Here, T represents transmittance, and d represents the thickness of the polarizer.

[0360] Based on the calculated ko[λ] and ke[λ], the absorbance and dichroism ratio in the in-plane and thickness directions can be calculated, thereby confirming whether the orientation is horizontal.

[0361] 〔use〕

[0362] The optical film of the present invention is not limited thereto, but it is preferred to be used for preventing peeping or controlling the viewing angle range of the display device.

[0363] [Display device]

[0364] The display device (image display device) of the present invention includes an optical film having the above-described polarizer and a display element.

[0365] The display element is preferably disposed on the polarizer side of the optical film (i.e., the side opposite to the transparent film substrate). The polarizer and the liquid crystal cell can be stacked via a known adhesive layer or bonding layer.

[0366] The display element used in the display device of the present invention is not particularly limited, and examples include liquid crystal cells, organic electroluminescent (hereinafter referred to as "EL") display panels and plasma display panels.

[0367] Preferably, a liquid crystal cell or an organic EL display panel is used. That is, as the display device of the present invention, a liquid crystal display device that uses a liquid crystal cell as a display element or an organic EL display device that uses an organic EL display panel as a display element is preferred.

[0368] Image display devices include thin ones that can be formed on curved surfaces. The optical anisotropic absorption film used in this invention is thin and easily foldable, and therefore is also preferably suitable for image display devices with curved display surfaces.

[0369] Furthermore, there are image display devices with pixel densities exceeding 250 ppi that are capable of high-definition display. The optical anisotropic absorption film used in this invention does not produce interference ripples and is therefore preferably suitable for such high-definition image display devices.

[0370] [Liquid Crystal Display Device]

[0371] As an example of the display device of the present invention, a liquid crystal display device is preferably provided that includes an optical film having the above-described polarizer and a liquid crystal cell.

[0372] As a specific structure, it has a configuration in which the optical film of the present invention is disposed on a front polarizer or a rear polarizer. In these configurations, viewing angle control is possible by blocking light in the vertical or horizontal directions.

[0373] Furthermore, the optical film of the present invention can be disposed on both the front polarizer and the rear polarizer. With this configuration, viewing angle control can be achieved, allowing light to be blocked from all directions and transmitted only from the front.

[0374] Furthermore, the optical film of the present invention can be laminated via a phase retardation layer. By controlling the phase difference value and the optical axis direction, the transmittance and light-blocking performance can be controlled. For example, by arranging a polarizer, an optical film, a λ / 2 wavelength plate (with an axial angle offset from the orientation direction of the polarizer by 45°), and an optical film, viewing angle control that allows light to be blocked from all directions and transmitted only from the front direction can be achieved. As the phase retardation layer, a positive A plate, a negative A plate, a positive C plate, a negative C plate, a B plate, an O plate, etc., can be used. From the viewpoint of making the viewing angle control system thinner, the thickness of the phase retardation layer is preferably thinner without impairing optical properties, mechanical properties, and manufacturing applicability. Specifically, it is preferably 1 to 150 μm, more preferably 1 to 70 μm, and even more preferably 1 to 30 μm.

[0375] The liquid crystal unit that constitutes a liquid crystal display device will be described in detail below.

[0376] <Liquid Crystal Unit>

[0377] The liquid crystal cells used in the liquid crystal display device are preferably in VA (Vertical Alignment) mode, OCB (Optically Compensated Bend) mode, IPS (In-Plane-Switching) mode or TN (Twisted Nematic) mode, but are not limited to these.

[0378] In TN mode liquid crystal cells, the rod-shaped liquid crystal molecules are substantially horizontally oriented when no voltage is applied, and then twisted to an orientation of 60–120°. TN mode liquid crystal cells are most commonly used in color TFT liquid crystal display devices and are documented in several publications.

[0379] In a VA-mode liquid crystal cell, the rod-shaped liquid crystal molecules are substantially vertically oriented when no voltage is applied. In a VA-mode liquid crystal cell, in addition to the narrow definition of a VA-mode liquid crystal cell which has rod-shaped liquid crystal molecules substantially vertically oriented when no voltage is applied and substantially horizontally oriented when a voltage is applied (as described in Japanese Patent Application Publication No. 2-176625), there are also (2) a liquid crystal cell in which the VA mode is multi-domainized (MVA mode) in order to expand the viewing angle (as described in SID97, Digest of Tech. Papers 28 (1997) 845), (3) a liquid crystal cell in which rod-shaped liquid crystal molecules are substantially vertically oriented when no voltage is applied and twisted into multi-domain orientation when a voltage is applied (n-ASM mode) (as described in the proceedings of the Japan Liquid Crystal Conference 58-59 (1998)), and (4) a SURVIVAL mode liquid crystal cell (published in LCD International 98). Furthermore, it can be any of the following: PVA (Patterned Vertical Alignment), Optical Alignment, and PSA (Polymer-Sustained Alignment). Detailed information about these modes can be found in Japanese Patent Application Publication Nos. 2006-215326 and 2008-538819.

[0380] In IPS-mode liquid crystal cells, the liquid crystal compound is substantially parallel to the substrate, and the liquid crystal molecules respond planarly by applying an electric field parallel to the substrate surface. That is, the liquid crystal compound is aligned in-plane in the absence of an applied electric field. Regarding the IPS mode, black is displayed in the absence of an applied electric field, and the absorption axes of the upper and lower polarizers are orthogonal to each other. Methods for reducing light leakage and improving viewing angle when displaying black in the oblique direction using optical compensation sheets are disclosed in Japanese Patent Application Publications Nos. 10-54982, 11-202323, 9-292522, 11-133408, 11-305217, and 10-307291.

[0381] [Organic EL display device]

[0382] As an example of the display device of the present invention, an organic EL display device may preferably be provided in a manner in which an optical film having the above-described polarizer, a λ / 4 plate, and an organic EL display panel are sequentially included from the visual recognition side.

[0383] Furthermore, similar to the liquid crystal display device described above, multiple optical films of the present invention can be stacked via a phase retardation layer and disposed on an organic EL display panel. By controlling the phase retardation value and the optical axis direction, the transmittance and light-blocking performance can be controlled.

[0384] Furthermore, an organic EL display panel is a display panel made of organic EL elements formed by sandwiching an organic light-emitting layer (organic electroluminescent layer) between electrodes (between the cathode and the anode). The structure of an organic EL display panel is not particularly limited and can adopt a known structure.

[0385] Example

[0386] The present invention will now be described in further detail based on embodiments. The materials, amounts, proportions, processing contents, and processing steps shown in the following embodiments can be appropriately modified without departing from the spirit of the invention. Therefore, the scope of the present invention should not be interpreted as limited by the embodiments shown below.

[0387] [Example 1]

[0388] The optical film A of Example 1 was manufactured as follows.

[0389] [Formation of Orientation Film 1]

[0390] The following alignment film forming composition 1 was continuously coated onto a cellulose acylated membrane (a 40 μm thick TAC substrate; TG40 FUJIFILM Corporation) using a wire rod. The support with the coating was dried in warm air at 140°C for 120 seconds to form alignment film 1, thus obtaining a TAC film 1 with the alignment film. The thickness of alignment film 1 was 0.5 μm.

[0391]

[0392]

[0393] [Chemical Formula 23]

[0394]

[0395] [Fabrication of Optical Anisotropic Film 1]

[0396] The liquid crystal composition 1 described below is continuously coated onto the obtained alignment film 1 using a wire rod. After heating at 120°C for 60 seconds, it is cooled to room temperature (23°C).

[0397] Next, heat at 85°C for 60 seconds, and then cool again to room temperature.

[0398] Then, using an LED (light emitting diode) lamp (center wavelength 365nm) at an illuminance of 200mW / cm² 2 The film was irradiated for 2 seconds under the specified irradiation conditions, thereby fabricating an optically anisotropic film 1 on the alignment film 1. The thickness of the optically anisotropic film 1 is 3.5 μm.

[0399]

[0400]

[0401] [Chemical Formula 24]

[0402]

[0403] [Chemical Formula 25]

[0404]

[0405] [Chemical Formula 26]

[0406]

[0407] [Formation of barrier layer B1]

[0408] The following color-adjusting layer forming composition B1 is continuously coated onto the obtained optical anisotropic film 1 using a wire rod to form a coating film.

[0409] Next, the support with the coating was dried in warm air at 60°C for 60 seconds, and then dried in warm air at 100°C for 120 seconds to form a tone adjustment layer G1, thus producing the optical film 1. The thickness of the barrier layer is 0.5 μm.

[0410]

[0411] Modified polyvinyl alcohol PVA-1

[0412] [Chemical Formula 27]

[0413]

[0414] [Comparative Example 1]

[0415] Using the liquid crystal composition H1 for optical anisotropic films, except that an optical anisotropic film and a barrier layer were formed on the cellulose acylate film in the same manner as in Example 1, an optical film H1 was produced.

[0416]

[0417]

[0418] [Example 2]

[0419] Using the liquid crystal composition 2 for optical anisotropic films, except that an optical anisotropic film and a barrier layer were formed on the cellulose acylate film in the same manner as in Example 1, an optical film 2 was fabricated.

[0420]

[0421] [Chemical Formula 28]

[0422]

[0423] [Chemical Formula 29]

[0424]

[0425] [Comparative Example 2]

[0426] Using the liquid crystal composition H2 for optical anisotropic films, except that an optical anisotropic film and a barrier layer were formed on the cellulose acylate film in the same manner as in Example 1, an optical film H2 was produced.

[0427]

[0428] [Chemical Formula 30]

[0429]

[0430] For the optically anisotropic film contained in the optical film of Example 1, a scanning transmission electron microscope image of the cross section is shown. Figure 4 Furthermore, the above methods (threshold setting, etc.) will be used to... Figure 4 The brightness binarized image of the scanning transmission electron microscope photograph is shown in Figure 5 .

[0431] Furthermore, for the optical anisotropic films contained in the optical films of Examples 1-2 and Comparative Examples 1-2, the length L of the major axis of the arrangement structure was measured by the above method. As a result, arrangement structures with a number of elements satisfying L≥30nm and arrangement structures satisfying L≥240nm, as shown in Table 1 below, were observed.

[0432] Furthermore, for the optical anisotropic films contained in the optical films of Examples 1-2 and Comparative Examples 1-2, the angle between the long axis of the arrangement structure and the normal direction of the optical anisotropic film was measured. The results are shown in Table 1 below.

[0433] Furthermore, the optical anisotropic films contained in the optical films of Examples 1 and 2 were evaluated according to the above-described method for evaluating vertical orientation. As a result, the liquid crystal compound and dichroic material contained in the optical anisotropic films were both vertically oriented.

[0434] [evaluate]

[0435] The following evaluation was conducted using the optical films of Examples 1-2 and Comparative Examples 1-2.

[0436] [Lightfastness]

[0437] The front transmittance (Tm0) of each optical film in the examples and comparative examples was measured using an AxoScan OPMF-1 (manufactured by Opto Science, Inc.). Then, the films were mounted on a lightfastness testing machine (Super Xenon Lamp Weathering Tester SX75; manufactured by Suga Test Instruments Co., Ltd.) at a xenon light incident angle of 60° and 50% RH at 150 W / m². 2 The film was subjected to 110 hours of xenon irradiation. The frontal transmittance (TX0) of the light-resistant film was measured in the same manner, and the lightfastness (ΔTxe) was evaluated using the following formula. The results are shown in Table 1 below.

[0438] ΔTxe=|Tm0-TX0|

[0439] A: ΔTxe is below 1.0%

[0440] B: ΔTxe is greater than 1.0 and less than 1.5

[0441] C: ΔTxe is greater than 1.5 and less than 3.0

[0442] D: ΔTxe is greater than 3.0

[0443] [Durability]

[0444] The front transmittance (Tm0) of each optical film of the Examples and Comparative Examples was measured in the same manner as the lightfastness evaluation.

[0445] Next, each optical film was mounted on a heat resistance tester at 95°C and 25% RH (relative humidity) and heated for 110 hours.

[0446] The frontal transmittance (TH0) of the heated film was measured in the same manner, and the lightfastness (ΔTH) was evaluated using the following formula.

[0447] ΔTH=|Tm0-TH0|

[0448] A: ΔTxe is below 3.0%

[0449] B: ΔTxe is greater than 3.0 and less than 5.0

[0450] C: ΔTxe is greater than 5.0 and less than 10.0

[0451] D: ΔTxe > 10.0

[0452] [Contrast]

[0453] Using the optical films of the examples and comparative examples, and employing an AxoScan OPMF-1 (manufactured by Opto Science, Inc.), the Mueller matrix of the optical films at wavelength λ was measured every 10 degrees between polar angles of -60 degrees and 60 degrees. After removing the influence of surface reflection, the transmittance (Tm0) at the front and the transmittance at 30° (Tm30) were calculated, and the contrast ratio (CR) was evaluated using the following formula.

[0454] CR = Tm0 / Tm30

[0455] A: Cr is 2.97 or higher.

[0456] B: Cr less than 2.97 and greater than 1.69

[0457] C: Cr less than 1.69 and greater than 1.27

[0458] D: Cr less than 1.27 and greater than 1.10

[0459] E: Cr less than 1.10

[0460] [Table 1]

[0461]

[0462] [Manufacturing of display devices]

[0463] [The formation of the tone adjustment layer G1]

[0464] The following color-adjusting layer forming composition G1 was continuously coated onto the optical anisotropic film 1 obtained in Example 1 using a wire rod to form a coating film.

[0465] Next, the support with the coating was dried in warm air at 60°C for 60 seconds, and then dried in warm air at 100°C for 120 seconds to form a tone adjustment layer G1, thus producing the optical film 1a. The thickness of the tone adjustment layer is 0.5 μm.

[0466]

[0467] [Chemical Formula 31]

[0468]

[0469] [Fabrication of optical laminate A1]

[0470] A polarizer 1 with a thickness of 8 μm and one side of the polarizer exposed was fabricated using the same method as that described in International Publication No. 2015 / 166991 for a polarizer 02 with a protective film on one side.

[0471] The exposed surface of the polarizer of polarizer 1 and the surface of the tone adjustment layer of the optical film 1a were corona treated, and then bonded together using the PVA adhesive 1 described below to create an optical laminate A1.

[0472] <Preparation of PVA Adhesive 1>

[0473] A 3.7% aqueous solution was prepared by dissolving 20 parts of hydroxymethyl melamine in pure water at a temperature of 30°C relative to 100 parts of polyvinyl alcohol resin containing acetylacetyl groups (average degree of polymerization: 1200, degree of saponification: 98.5 mol%, degree of acetylacetylation: 5 mol%).

[0474] [The fabrication of image display device A1]

[0475] An iPad Air Wi-Fi model 16GB (manufactured by Apple Inc.), an IPS-mode liquid crystal display device, was disassembled, and the liquid crystal cell was removed. The visual recognition side polarizer was peeled off from the liquid crystal cell. Using adhesive sheet 1, the aforementioned laminate A1 was bonded to the surface where the visual recognition side polarizer was removed, so that the polarizer 1 side became the liquid crystal cell side. At this time, the absorption axis of the polarizer 1 was aligned with the absorption axis of the visual recognition side polarizer bonded to the product. After bonding, it was reassembled to manufacture the image display device A1.

[0476] (Preparation of Adhesive Sheet 1)

[0477] Acrylate polymers were prepared according to the following steps.

[0478] In a reaction vessel equipped with a cooling pipe, a nitrogen inlet pipe, a thermometer, and a stirring device, 95 parts by weight of butyl acrylate and 5 parts by weight of acrylic acid were polymerized by solution polymerization to obtain an acrylate polymer A1 with an average molecular weight of 2 million and a molecular weight distribution (Mw / Mn) of 3.0.

[0479] Next, in addition to the obtained acrylate polymer A1 (100 parts by mass), a 75% by mass ethyl acetate solution of CORONATE L (a trimethylolpropane adduct of toluene diisocyanate, 3 isocyanate groups per molecule, manufactured by Nippon Polyurethane Industry Co., Ltd.) (1.0 part by mass) and a silane coupling agent KBM-403 (manufactured by Shin-Etsu Chemical Co., Ltd.) (0.2 parts by mass) were mixed. Finally, ethyl acetate was added to bring the total solids concentration to 10% by mass, thus preparing an adhesive-forming composition. This composition was coated onto a separation membrane that had been surface-treated with a silicone-based stripper using a die coater and dried at 90°C for 1 minute to obtain an acrylate adhesive sheet. The film thickness was 25 μm, and the storage modulus was 0.1 MPa.

[0480] The image display device manufactured in Example 1 was used to display white, and as a result, the tones from both the front and the oblique sides were neutral.

[0481] Symbol Explanation

[0482] P - Optical anisotropic film, M - (molecule of the first dichroic substance), O - (molecule of the second dichroic substance), L - (molecule of the liquid crystal compound), G - aggregate, w - width, a - angle.

Claims

1. An optically anisotropic film comprising a liquid crystal compound and a dichroic substance, wherein, The liquid crystal compound is vertically oriented. The dichroic substance forms an arrangement structure. In a cross-section observed by scanning transmission electron microscopy, with the length of the major axis of the arrangement structure denoted as L and the length of the minor axis as D, an arrangement structure satisfying 30nm ≤ L ≤ 240nm is found to be present in every 40μm. 2 More than 16 were observed in the study. In the arrangement structure, the proportion of arrangement structures in which the angle between the major axis of the arrangement structure and the normal direction of the optical anisotropic film is 20° or more is 28.0% or more.

2. The optical anisotropic film according to claim 1, wherein, An arrangement structure satisfying L≥240nm per 40μm 2 Less than 3 were observed.

3. An optical film having: Transparent film substrate; and The optical anisotropic film of claim 1 or 2 disposed on the transparent film substrate.

4. The optical film according to claim 3, wherein, The optical film also has an alignment film between the transparent film substrate and the optical anisotropic film.

5. The optical film according to claim 3, wherein, The optical film also has a polarizer with an in-plane absorption axis and is used to control the viewing angle.

6. A display device having the optical film and display element as described in claim 5.

Citation Information

Patent Citations

  • JP1975048120A

  • Irokeshitaibutsurenzu

    JP1976043918A

  • Photosensitive compound containing trichloromethyl group, manufacture and photosensitive mixture

    JP1985105667A

  • Acylphosphine oxide compound*its manufacture and its use

    JP1988040799B2

  • thawer

    JP1988230032A